Thrips pollination of Mesozoic gymnosperms - Peñalver, Enrique (National Academy of Sciences, 2012)
Within modern gymnosperms, conifers and Ginkgo are exclusively wind pollinated whereas many gnetaleans and cycads are insect pollinated. For cycads, thrips are specialized pollinators. We report such a specialized pollination mode from Early Cretaceous amber of Spain, wherein four female thrips representing a genus and two species in the family Melanthripidae were covered by abundant Cycadopites pollen grains. These females bear unique ring setae interpreted as specialized structures for pollen grain collection, functionally equivalent to the hook-tipped sensilla and plumose setae on the bodies of bees. The most parsimonious explanation for this structure is parental food provisioning for larvae, indicating subsociality. This association provides direct evidence of specialized collection and transportation of pollen grains and likely gymnosperm pollination by 110–105 million years ago, possibly considerably earlier.